Implication of Topical Steroids in the Onset of Osteoporosis - Milyani, Asmaa Adel (Case Rep Pediatr, 2018)
The systemic bioavailability of steroids has long been implicated as a cause for osteoporosis (OP); however, much less is known about the effect of topical steroids on bone homeostasis. This is a case of an 11-year-old male who is a known case of generalised pustular psoriasis for 8-year duration with frequent exacerbations controlled with topical betamethasone dipropionate. He presented with generalised progressive bone pain and positive history of bone fracture. The diagnosis of OP was established on the results of DEXA, which were −2.7 SD and −2.4 SD for the lumbar spine and whole body, respectively. Although the cutoff value is the same (<−2 SD) in children, the definition of OP is more reliant on the densitometry Z score, as opposed to adults, who are approached using the T score. The element of psoriasis poses a risk for the development of OP due to the presence of a chronic inflammatory disease state that increases bone turnover. Furthermore, the compromised skin barrier and associated vasodilation seen in psoriasis enhance the absorption of topically applied agents and increase their bioavailability. Children are a targeted risk group as they are more vulnerable to the manifestation of systemic adverse affects of topically applied steroids as a result of their increased ratio of total surface area relative to their body weight and slower drug metabolism. We recommend that children undergoing long-term topical steroid therapy be screened for OP with the consideration of instituting prophylactic treatment especially in those suffering from chronic inflammatory disease states.